THEORY ANALYSIS OF THE APPLICATION OF THE NATIONAL-REGIONAL COMPONENT TO THE PRACTICE OF TEACHING FINE ARTS IN SECONDARY SCHOOLS (Multidisciplinary Journal of Science and Technology, 2026)
This article comprehensively analyzes research and theory related to ethno-cultural competence in the field of art education. Ethnomathean competence, which includes the ability to understand, appreciate and effectively deal with individuals from different cultures, is increasingly recognized as an important component of modern educational practice.